Care robots for the common good: ethics as politics - Núria Vallès-Peris; Miquel Domènech (Humanities & Social Sciences Communications, 2023)
The development of care robots has been accompanied by a number of technical and social challenges, which are guided by the question: “What is a robot for?” Debates guided by this question have discussed the functionalities and tasks that can be delegated to a machine that does not harm human dignity. However, we argue that these ethical debates do not offer any alternatives for designing care robots for the common good. In particular, we stress the need to shift the current ethical discussion on care robots towards a reflection on the politics of robotics, understanding politics as the search for the common good. To develop this proposal, we use the theoretical perspective of science and technology studies, which we integrate into the analysis of disagreement inspired by a consensus-dissensus way of thinking, based on discussing and rethinking the relationships of care robots with the common good and the subjects of such good. Thus, the politics of care robots allows for the emergence of a set of discussions on how human-machine configurations are designed and practiced, as well as the role of the market of technological innovation in the organisation of care.